Positives and negatives of nonsteroidal anti-inflammatory drugs in bone healing: the effects of these drugs on bone repair - Lisowska B; Kosson D; Domaracka K (Dove Medical Press, 2018)
Barbara Lisowska,1 Dariusz Kosson,2 Karolina Domaracka3 1Department of Anesthesiology and Intensive Care, John Paul II Western Hospital, Grodzisk Mazowiecki, Poland; 2Department of Anaesthesiology and Intensive Care, Medical University of Warsaw, Division of Teaching Warsaw, Warsaw, Poland; 3Department of Anaesthesiology and Intensive Care, Medical University of Warsaw, Warsaw, Poland Abstract: Tissue damage following injury triggers the processes of coagulation, inflammation and healing. In tissues surrounding the bone, the result of the healing process is a scar, while bone tissue has a unique ability to achieve shape, strength and pre-injury function. Bone healing is a process of regeneration rather than classic recovery. The result of this process is the formation of new, healthy bone tissue instead of a scar. Many factors can inhibit or impair the bone healing process, and their influence is critical during the stages of inflammation and angiogenesis and finally on the clinical outcome. Nonsteroidal anti-inflammatory drugs (NSAIDs) play an essential role associated with their analgesic potency and anti-inflammatory effects. NSAIDs are also the most often used drugs in patients who require pain control and inflammation reduction due to musculoskeletal diseases or injures. Although their analgesic effect is well documented, NSAIDs also interfere with bone healing; therefore, the relative benefits and disadvantages connected with their administration should be taken into consideration. Despite the negative effect, NSAIDs have beneficial properties, but their clinical benefits in relation to dose and time of use are still unclear. Therefore, in this review, we focus on bone healing with relation to the impact of NSAIDs. Keywords: bone healing, NSAIDs, negative, positive effect